THE EFFECT OF LIQUIDITY AND LEVERAGE ON FINANCIAL DISTRESS WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE IN MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Inayatul Maula; Acep Komara (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study's goal is to investigate how leverage and liquidity ratios affect financial crisis, with sound corporate governance acting as a moderating factor. This study uses an associative technique and a quantitative approach. Secondary data from the financial statements of businesses listed between 2020 - 2024 on the IDX makes up the data utilized. The sample was chosen via purposeful sampling. Forty yearly financial reports were examined in this study. The data analysis included both moderated regression analysis and multiple linear regression. The results show that financial hardship is positively and significantly impacted by liquidity and leverage. The link between liquidity, leverage, and financial distress is not moderated by GCG (Independent Commissioners). Leverage and liquidity have a 16.8% impact on financial distress.